2002
DOI: 10.1021/ja012267j
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Unfolding and Folding of Gaseous Ubiquitin Ions Characterized by Electron Capture Dissociation

Abstract: The unfolding enthalpy of the native state of ubiquitin in solution is 5 to 8 times that of its gaseous ions, as determined by electron capture dissociation (ECD) mass spectrometry. Although two-state folding occurs in solution, the three-state gaseous process proposed for this by Clemmer and co-workers based on ion mobility data is supported in general by ECD mass spectra, including relative product yields, distinct Delta H(unfolding) values between states, site-specific melting temperatures, and folding kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
459
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(500 citation statements)
references
References 45 publications
35
459
1
5
Order By: Relevance
“…The loss of SH 2 is somewhat surprising, as the loss of a sulfur would be expected to lead to the separation of the two peptide chains. The observed loss of only SH 2 might be explained by either a rearrangement to form a monosulfide bond between the two peptide chains, or by the existence of noncovalent bonding between the chains that might hold them together°after°disulfide°bond°cleavage° [43].°The°dearth of backbone cleavages and the relatively abundant chain ions observed in the reaction product ions of Figure°1°indicate°that°the°disulfide°bonds°are°cleaved preferentially to the backbone bonds upon electron transfer in this reaction. Previous work with ECD has also shown a preference for cleavage of the disulfide bond° [24].…”
Section: Electron Transfer With Dissociationmentioning
confidence: 96%
See 2 more Smart Citations
“…The loss of SH 2 is somewhat surprising, as the loss of a sulfur would be expected to lead to the separation of the two peptide chains. The observed loss of only SH 2 might be explained by either a rearrangement to form a monosulfide bond between the two peptide chains, or by the existence of noncovalent bonding between the chains that might hold them together°after°disulfide°bond°cleavage° [43].°The°dearth of backbone cleavages and the relatively abundant chain ions observed in the reaction product ions of Figure°1°indicate°that°the°disulfide°bonds°are°cleaved preferentially to the backbone bonds upon electron transfer in this reaction. Previous work with ECD has also shown a preference for cleavage of the disulfide bond° [24].…”
Section: Electron Transfer With Dissociationmentioning
confidence: 96%
“…Two hypotheses can be proposed to account for how electron transfer can occur without leading to discrete fragments. In the first, a covalent bond is broken, but the fragments remain bound via noncovalent°interactions° [43].°In°the°second,°a°bond°may°be significantly°weakened°by°the°electron°transfer° [47],°but the dissociation rate is sufficiently slow relative to cooling rates in the ion trap to allow for at least some of the electron transfer products to be stabilized. The latter interpretation assumes that the covalent bonds in the electron transfer products are sufficiently strong to survive under the normal ion trap storage conditions.…”
Section: Electron Transfer Without Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in ECD behavior between proteins have been attributed to conformational differences. 11,38 It has been shown that gas-phase structures of a single protein differ between specific charge states and even differ for the same charge state. 39 Increasing Coulomb repulsion through an increase of the number Figure 5.…”
Section: Scheme 1 Reaction Pathways Of Gp31 21+ Upon Activation Usinmentioning
confidence: 99%
“…18 The second employed an on-axis hollow electron beam for high-rate ECD, while the IR laser beam was kept on-axis. 19 The application area of high-rate ECD/FTICR-MS is growing rapidly, currently covering the de novo sequencing and sequence verification of peptides and proteins, 24 characterization of post-translational modifications in peptides and proteins, 24,31 revealing the secondary and tertiary structures of proteins, 32 studies of protein folding/unfolding dynamics, 33,34 and analysis of complex biological mixtures by on-line and off-line combination of ECD and LC(CE)/FTICR-MS. 27 -29,35 The present paper presents an overview of selected applications of high-rate ECD/FTICR-MS in peptide and protein characterization, preceded by a short description of the basic features of ECD and current experimental configurations.…”
Section: Introductionmentioning
confidence: 99%